Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.3 Polynomials - R.3 Exercises - Page 32: 25



Work Step by Step

RECALL: (1) $(ab)^m=a^mb^m$ (2) $(a^m)^n=a^{mn}$ Use rule (1) above to obtain: $=(-6)^3(x^2)^3 \\=-6(-6)(-6)(x^2)^3 \\=-216(x^2)^3$ Use rule (2) above to obtain: $=-216(x^{2(3)}) \\=-216x^6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.